Pemanfaatan Beras Jimpitan Untuk Kemakmuran Masjid - Daulay, Aswan; Husni, Annisa Aulia; Fajar, Aulia; Putri, Bella Diana; Pangaribuan, Dela Safitri; Dania, Nur; Reza, Muhammad; N, Nurhafizah; Marpaung, Rani Nirmala; Fauzi, Rifki Ahmad; S, Suratini; Panjaitan, Wildan (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
This journal examines the utilization of rice as a resource to enhance the prosperity of mosques and their surrounding communities. Mosques serve not only as places of worship but also as social centers that empower society. The research explores various initiatives, including rice aid programs for needy congregants, the organization of social activities, and the development of mosque-based microenterprises. Through surveys and interviews with mosque administrators, it was found that effective strategies for utilizing rice can increase community engagement, strengthen solidarity, and support local economic stability. The findings of this study are expected to guide mosque managers in formulating innovative and sustainable programs.